Minimally invasive aortic valve replacement: extracorporeal circulation optimization and minimally invasive extracorporeal circulation system evolution. (November 2020) - Carozza, Roberto; Fazzi, Diego; Pietrini, Armando; Cefarelli, Mariano; Mazzocca, Francesca; Vessella, Walter; Berretta, Paolo; Romagnoli, Monica; Alfonsi, Jacopo; Zahedi, Hossein M.; Munch, Christopher; Di Eusanio, Marco
Treatment of aortic valve disease has become less and less invasive during the last years, thanks to progress in anesthesiology, surgical techniques, and perfusion management. In fact, it has been demonstrated that shorter skin incision, combined with ultra-fast-track anesthesia and minimized extracorporeal circuit could improve clinical outcomes. Current evidence shows that minimally invasive extracorporeal circulation system is associated with reduced red blood cells' transfusion rate, improved end-organ perfusion, decreased incidence of postoperative atrial fibrillation, air embolism leakage, and so less cerebral accidents with better neurological outcomes. Moreover, the use of a closed circuit seems to be more physiologic for the patients, reducing systemic inflammatory response due to less air–blood contact and the use of biocompatible surfaces. In the literature, the benefits of minimally invasive extracorporeal circulation are described mostly for coronary surgery but few data are nowadays available for minimally invasive extracorporeal circulation during aortic valve replacement. In this article, we describe our perfusion protocol in minimally invasive aortic valve replacement.